MENGKAJI PASAL-PASAL BIAS GENDER UU PERKAWINAN: Tawaran Pencegahan Kekerasan Terhadap Perempuan - L, Lufaefi (IAIN Tulungagung, 2018)
Man is created into a man and a woman. Both have equal rights in the perspective of God (Surat AtTaubah [9]: 71-72). But, as a matter of fact women often become marginalized person. One example is as illustrated in the contents of several articles of Indonesian marriage laws which are still gender- biased and discredit women. This applies in the definition of marriage which inferiorly disparages women; women's marriage age should be easier than men; legalized polygamy; the inferior position of the wife in the point of view of the husband and many other problems. This article is trying to see those problems from the perspective of religion, however violating the religious ideals that require justice. Therefore the solution of the problems is sought to fit with the ideals of religion. Through the approach of Islam, the above mentioned examples are contradictory to the teachings of Islam, because it is not in line with the vision of religion as a religion of justice, equality and glorification of women.Keywords: UUP, Gender Bias, Women, Equality